Evaluation of Renal Function Before and After Percutaneous Mitral Valve Repair. (January 2015) - Wang, Andrew; Sangli, Chithra; Lim, Scott; Ailawadi, Gorav; Kar, Saibal; Herrmann, Howard C.; Grayburn, Paul; Foster, Elyse; Weissman, Neil J.; Glower, Donald; Feldman, Ted
<x xml:space="preserve">Abstract</x> Background— Chronic kidney disease (CKD) is strongly related to outcome in cardiovascular diseases. The relationship between treatment of mitral regurgitation (MR) and renal function is not well described. We sought to evaluate renal function before and after mitral valve repair by the MitraClip device. Methods and Results— Patients with moderate-to-severe or severe (3+ or 4+, respectively) MR by core laboratory determination who underwent transcatheter mitral valve repair with the MitraClip device in multicenter, investigational trials were included in this study. Estimated glomerular filtration rate (eGFR) was evaluated before and at hospital discharge, 30 days, 6 months, and 1 year after mitral valve repair. Eight hundred fifty-four patients with baseline mean eGFR 61.5±23.1 mL/min/1.73 m2 were studied, including 438 (51.3%) with eGFR ≥60 mL/min/1.73 m2 (CKD stage 1 or 2), 371 (42.6%) with eGFR 30 to 59 mL/min/1.73 m2 (CKD stage 3), and 52 (6.1%) with eGFR <30 mL/min/1.73 m2 (CKD stage 4 or 5). Baseline renal dysfunction was more prevalent in older patients with a history of heart failure, coronary artery disease, cerebrovascular disease, diabetes mellitus, hypertension, and atrial fibrillation. Baseline eGFR was associated with 1-year survival (P<0.001) after MitraClip repair. At 1-year follow-up, the mean change in eGFR for the overall cohort was −1.0±15.1 mL/min/1.73 m2; for patients with CKD stage 1 or 2, stage 3, or stage 4 or 5, mean change was −4.1±16.6, +2.6±12.4, and +4.8±9.5 mL/min/1.73 m2, respectively. Linear mixed effect modeling demonstrated a strong association between MR and eGFR, and a statistically significant improvement in eGFR in patients with CKD stage 4 or 5 associated with MR reduction to ⩽2+ (P=0.007). Conclusions— Renal dysfunction is associated with lower survival in patients with severe MR even after percutaneous mitral valve repair. Reduction in MR severity by the MitraClip device is associated with improvement in renal function at 1 year in patients with baseline renal dysfunction. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifiers: NCT00209274, NCT01931956, NCT01940120.